Ecological footprint and the wealth of people from a socio-ecological point of view - Mulyawan, Muhammad Fathurrahman; Antriyandarti, Ernoiz; Son, Ho Ngoc (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2024)
With time it is getting more difficult to solve environmental issues as several people are unaware of the current environmental concerns. Using the ecological footprint analysis, people can know their daily use of natural resources. Therefore, this study aims to determine the ecological footprint of people in Solo, Indonesia. We applied the Ecological Footprint Test to the 152 respondents that consist of students, academicians and ordinary people. Through survey and questionnaire, this study found the relationship between different statuses of occupation and determined which category was more eco-friendly. Furthermore, this study hypothesized about the effects of education level on the use of natural resources and explained that educational level does affect the use of natural resources. Regression analysis was used to examine the determinant of ecological footprint score of the Solo people. The result showed that the estimated parameter of education has positively significant to the ecological footprint of the people of Solo. The higher the education, the higher the ecological footprint score of the Solo people. This is indirectly related to mobility and the goal of earning more income for those with higher education. Therefore, their consumption of natural resources is higher than that of ordinary people. TheÂ  economic improvement is directly proportional to increases in income and natural resources.JEL ClassificationÂ P18; Q01; Q30To cite this article: Mulyawan, M. F., Antriyandarti, E., & and Son, H. N. (2024). Ecological footprint and the wealth of people from a socio-ecological point of view. Journal of Socioeconomics and Development, 7(1), 14-23. https://doi.org/10.31328/jsed.v7i1.4218